Copper/copper oxide nanoparticles synthesis using Stachys lavandulifolia and its antibacterial activity - Khatami, Mehrdad; Heli, Hossein; Jahani, Peyman Mohammadzadeh; Azizi, Hakim; Nobre, Marcos Augusto Lima [UNESP] (Institution of Engineering and Technology (IET), 2017)
Nanoparticles of copper/cuprous oxide (Cu/Cu2O) were successfully synthesised by a green chemistry route. The synthesis process was carried out using an extract of Stachys lavandulifolia as both reducing and capping agents with a facile procedure. The nanoparticles were characterised by different techniques including X-ray diffraction, indicating that the synthesised sample comprised both copper and cuprous oxide entity. The nanoparticles had a mean size of 80 nm and represented an impressive bactericidal effect on Pseudomonas aeruginosa.